2022
DOI: 10.3390/diagnostics12092180
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization by Whole-Genome Sequencing of Clinical and Environmental Serratia marcescens Strains Isolated during an Outbreak in a Neonatal Intensive Care Unit (NICU)

Abstract: The whole-genome sequencing (WGS) of eighteen S. marcescens clinical strains isolated from 18 newborns hospitalized in the Neonatal Intensive Care Unit (NICU) at Pescara Public Hospital, Italy, was compared with that of S. marcescens isolated from cradles surfaces in the same ward. The identical antibiotic resistance genes (ARGs) and virulence factors were found in both clinical and environmental S. marcescens strains. The aac(6′)-Ic, tetA(41), blaSRT-3, adeFGH, rsmA, and PBP3 (D350N) genes were identified in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 59 publications
1
6
0
Order By: Relevance
“…Examination of virulence factors showed that differences were most influenced by phylogroup lineage. This finding is consistent with both the Piccirilli et al [29] and Abreo and Altier [18] studies, wherein PCA data showed no relationship found between virulence factors of clinical versus environmental samples. Instead, virulence factors were typically more similar within the same cluster on the phylogenetic tree than between them.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Examination of virulence factors showed that differences were most influenced by phylogroup lineage. This finding is consistent with both the Piccirilli et al [29] and Abreo and Altier [18] studies, wherein PCA data showed no relationship found between virulence factors of clinical versus environmental samples. Instead, virulence factors were typically more similar within the same cluster on the phylogenetic tree than between them.…”
Section: Discussionsupporting
confidence: 91%
“…Franczek et al [28] found that mannose-resistant type-K hemagglutination virulence factor was statistically higher in clinical samples out of a total of 147 S. marcescens strains. Piccirilli et al [29] reported that both environmental and clinical sequences of S. marcescens from a neonatal outbreak had identical antibiotic resistance genes and virulence factors. As in this study, a comparison of 49 S. marcescens strains found on GenBank by Abreo and Altier [18] found that differences related to virulence factors were apparently more influenced by phylogeny rather than source (environmental versus clinical) of strains.…”
Section: Discussionmentioning
confidence: 99%
“…The bacterium is able to survive on various surfaces, including soap, and to rapidly spread among hospital patients, causing large nosocomial outbreaks, particularly in NICUs. 16 , 27 , 28 , 29 , 30 , 31 , 32 S. marcescens mainly colonize the environment (soil, plants, and animals) and recent genomic studies revealed that the nosocomial S. marcescens infections are mostly caused by a specific lineage of the bacterium (here called “Infectious clone”). 3 , 6 , 7 Considering the lethality of the bacterium, its fast-spreading capability and the existence of a strictly infection-associated lineage, a fast and precise detecting/typing method is required to establish effective infection control strategies in hospitals to prevent and to limit outbreaks.…”
Section: Discussionmentioning
confidence: 99%
“…Lately, carbapenemase-producing strains of S. marcescens have been found more frequently. This represents a severe risk because this organism is intrinsically resistant to colistin, which is considered the last drug option for carbapenem-resistant infections [ 39 ].…”
Section: Discussionmentioning
confidence: 99%